Skills and Europe's Labor Market How Technological Change and Other Drivers of Skill Demand and Supply are Shaping Europe's Labor Market - Hoftijzer, Margo (World Bank E-Library Archive, 2018)
This report complements the recent World Bank publication, Growing United: Upgrading Europe's Convergence Machine (Bodewig, C., Ridao-Cano, C., 2018). The Growing United report highlights that, while the European Union is still the "convergence machine" that fosters an unparalleled depth and scope of regional economic integration, it is no longer working for everyone. The report points to a growing divide, reflected in inequality widening among households across and within EU countries. It reviews the underlying factors of this growing divide from two angles, that of people and that of firms, and for both it examines the reasons why some are left behind and others thrive. This review of labor market trends, the underlying causes that determine which skills are in demand, and how they are rewarded, starts with a framing chapter, briefly summarizing trends in inequity in the EU and ongoing discourse on the impact of technological change and other driver of skill demand and supply on labor outcomes. This is followed by a brief description of trend in employment and earnings in the EU since the late 1990's (chapter two); and a brief description of factors that shape skill demand (technology, globalization, aging, and the level of economic development) followed by an analysis of the evolution of the task content of jobs (chapter three). It then proceeds to discuss the parallel impact of supply-side factors, like education and migration, on the resulting labor market trends; and finally proposes an analytical framework to understand the extent to which the interaction of demand and supply factors is altering the labor market structure in the EU (chapter five)